2019
DOI: 10.1021/acs.energyfuels.9b03630
|View full text |Cite
|
Sign up to set email alerts
|

Change in Catalytic Activity of Potassium during CO2 Gasification of Char

Abstract: Potassium (K)-catalyzed CO 2 gasification of lignite char was studied with a particular focus on the change in catalyst activity with the char conversion (X) at 800−900 °C. Char samples were prepared from an Indonesian lignite by a sequence of complete removal of inherent metallic species and mineral matter, K-loading by ion-exchange, and pyrolysis. The catalytic activity of K (k cat ′ ) was defined as the rate of catalytic gasification (after elimination of the rate of non-catalytic gasification and that of K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 51 publications
(135 reference statements)
1
3
1
Order By: Relevance
“…At 800 °C, the instantaneous rate is sharply increased at the initial stage of conversion, as shown in Figure b (left insert), also observed at 750 °C (see Supporting Information) but to a lower degree, whereas it was not found for 700 °C. In view of the experimental reactivity rate versus conversion, this results in a conversion progression exhibiting two peaks, as displayed in Figure , a pattern also observed in other studies. , …”
Section: Results and Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…At 800 °C, the instantaneous rate is sharply increased at the initial stage of conversion, as shown in Figure b (left insert), also observed at 750 °C (see Supporting Information) but to a lower degree, whereas it was not found for 700 °C. In view of the experimental reactivity rate versus conversion, this results in a conversion progression exhibiting two peaks, as displayed in Figure , a pattern also observed in other studies. , …”
Section: Results and Discussionsupporting
confidence: 83%
“…In the present study, an inflection point of K where R starts to decrease, as identified for the high-ash containing char and potassium-impregnated coal char gasification, ,,, was not observed. Additionally, the determined increase of the instantaneous reaction rate as shown in Figure is not proportional, as reported by Karlström et al, who observed a proportionality between the instantaneous conversion rate and the K/C ratio in the conversion range of 0 to 80% during CO 2 char gasification of K-rich agricultural biomass.…”
Section: Results and Discussioncontrasting
confidence: 55%
See 3 more Smart Citations